The INFLUENCE OF DIGITAL LEADERSHIP AND EMPLOYEE DIGITAL COMPETENCY ON HUMAN RESOURCE PERFORMANCE THROUGH E-HRM TRANSFORMATION: A STUDY OF SAMSAT EMPLOYEES’ PERCEPTIONS - Fitri, Mahdaliyah; Rosita, Sry; Aurora Lubis, Tona (Journal of Business Studies and Management Review, 2025)
Digital transformation has become an important part of bureaucratic reform aimed at improving organizational efficiency and the quality of public services. This study aims to analyze the influence of digital leadership and employee digital competence on public service human resource performance, as well as examine the mediating role of electronic Human Resource Management (e-HRM) transformation in the SAMSAT Office of Jambi City. The study employed an explanatory quantitative approach using a survey method involving all employees of UPTD PPD SAMSAT Kota Jambi, totaling 80 respondents, through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that digital leadership has a positive and significant effect on human resource performance, but it does not have a significant effect on e-HRM transformation. Employee digital competence has a negative effect on human resource performance, but it has a positive and significant effect on e-HRM transformation. Furthermore, e-HRM transformation positively affects human resource performance. In the mediation analysis, e-HRM transformation does not mediate the relationship between digital leadership and human resource performance, but it significantly mediates the relationship between employee digital competence and human resource performance. These findings indicate that improving digital competence will be more effective in enhancing performance when supported by the implementation of an integrated e-HRM system. This study contributes to the development of digital-based public sector human resource management studies and provides practical recommendations for improving the quality of public services.